(untitled) (Journal of Engineering, 2015)
In wireless broadband communications using single-carrier interleave division multiple access (SC-IDMA) systems, efficient multiuser detection (MUD) classes that make use of joint hybrid decision feedback equalization (HDFE)/ frequency decision-feedback equalization (FDFE) and interference cancellation (IC) techniques, are proposed in conjunction with channel coding to deal with several users accessing the multipath fading channels. In FDFE-IDMA, the feedforward (FF) and feedback (FB) filtering operations of FDFE, which use to remove intersymbol interference (ISI), are implemented by Fast Fourier Transforms (FFTs), while in HDFE-IDMA the only FF filter is implemented by FFTs. Further, the parameters involved in the FDFE/HDFE filtering are derived according to the minimum mean square error (MMSE) criteria, and the feedback symbol decisions are directly designed from soft detection of the decoded signals at the previous iteration. The simulation results including comparisons with those of frequency domain equalization (FDE), SC-FDE-IDMA and multi-carrier OFDM-IDMA schemes, with cyclic prefixing (CP) and zero padding (ZP) techniques, show that the combination of FDFE-IC/HDFE-IC provides an efficient solution with good performance for IDMA systems in ISI channels. Moreover, these iterative structures with block equalization yield a much lower complexity than equivalent existing structures, making them attractive for a wealth of applications.